Prognostic implications of microcirculatory perfusion versus macrocirculatory perfusion in cardiogenic shock: a CULPRIT-SHOCK substudy. Issue 2 (1st March 2020) - Wijntjens, Gilbert W M; Fengler, Karl; Fuernau, Georg; Jung, Christian; den Uil, Corstiaan; Akin, Sakir; van de Hoef, Tim P; Šerpytis, Rokas; Diletti, Roberto; Henriques, José P S; Šerpytis, Pranas; Thiele, Holger; et al.
Abstract: Background: After early revascularisation, restoration of macrocirculatory perfusion parameters is the primary objective in the management of cardiogenic shock complicated acute myocardial infarction. Nevertheless, vital organ perfusion may be compromised at the systemic microcirculatory level, even in patients with preserved macrohaemodynamics. Microvascular perfusion was shown to have independent prognostic value for early mortality. The present study aims to compare the prognostic value of microcirculatory versus macrocirculatory perfusion parameters. Methods: This substudy of the culprit lesion-only percutaneous coronary intervention versus multivessel percutaneous coronary intervention in cardiogenic shock (CULPRIT-SHOCK) trial examined the sublingual capillary network using videomicroscopy post-percutaneous coronary intervention to determine the proportion of perfused capillaries (<20 µm) and perfused capillary density. Thirty-day follow-up was performed to obtain the occurrence of a combined clinical endpoint of all-cause death and renal replacement therapy. Results: Videomicroscopy measurements were performed in 66 patients. There was a significant adjusted association between microcirculatory perfusion parameters and the combined clinical endpoint (proportion of perfused capillaries: P =0.020; perfused capillary density: P =0.035), whereas there was no significant adjusted association between macrocirculatory perfusion parameters and the combined clinical endpoint (systolic blood pressure: P =0.205). Normotensive patients with compromised microcirculatory perfusion parameters had a higher risk of the combined clinical endpoint than normotensive patients with preserved microcirculatory perfusion parameters (proportion of perfused capillaries: Breslow P =0.014; perfused capillary density: Breslow P =0.076). Conclusions: There is a significant and independent association between microcirculatory perfusion parameters perfused capillary density and proportion of perfused capillaries and the combined clinical endpoint of all-cause death and renal replacement therapy at 30 days follow-up. In patients with loss of haemodynamic coherence between microcirculatory and macrocirculatory perfusion parameters, microcirculatory perfusion parameters confer dominant prognostic value.